A Review of Benefits, Challenges, and Strategies of Students’ Oral Presentation in Higher Education - Chhayna Cheng (CV. Samuel Manurung and Co, 2025)
Although a growing body of research has assessed students’ oral presentations in higher education, a comprehensive and unified exploration of their benefits, challenges, and strategies remains limited. This review aims to fill this knowledge gap by integrating and analyzing these aspects into a cohesive framework. Using a literature review approach, document analysis, and specific inclusion criteria, 104 articles were gathered from reliable sources and published between 2020 and 2025. By utilizing secondary data, the review reveals that oral presentation provides significant benefits for students, such as developing speaking skills, improving critical thinking, enhancing communication skills, and increasing academic engagement. However, several challenges go beyond these benefits, including students’ anxiety, levels of students’ knowledge, lack of adequate preparation, and body language issues, which can hinder students’ oral presentation performance. Therefore, this review highlights effective strategies across different contexts and organizations, such as reading engagement, script preparation, sufficient rehearsal, peer assessment, self-assessment, building self-confidence, and fostering self-motivation, all of which are essential for addressing challenges in higher education. Overall, this review suggests that future research should rigorously examine students’ oral presentations in higher education across various settings and institutions.